The Impact of Earthquake Disaster Mitigation Socialization on Improving Student Knowledge at SMAN1 Babakan Madang: Dampak Sosialisasi Mitigasi Bencana Gempa Bumi Terhadap Peningkatan Pengetahuan Siswa di SMAN1 Babakan Madang - Setiawan, Cahyadi; Munandar, Aris; Ramadhoan A' Rachman , Fauzi; Wahyu Wardana, Muhammad; Salsabillah , Fadia; Divino Wibowo , Josua; Furqon, Zidan; Agusman, Ridho; Putri Maulana, Amelia; Hidayat, Sahrul (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
SMAN 1 Babakan Madang is located in Bogor Regency, an area prone to earthquakes due to its proximity to the southern coast of Java Island and its position between three active faults: the Baribis Fault, the Citarik Fault, and the Cimandiri Fault. To mitigate risks and impacts, the PPM UNJ team provided training and simulations to enhance participants' knowledge and skills in responding to earthquakes. The impact of the knowledge enhancement was measured by the difference in average scores before and after the training. The number of participants and respondents in this activity was 55. Data analysis results showed an increase in participants' knowledge about earthquake disaster mitigation, reflected in the increase in average scores from 66.10 in the pre-test to 75.00 in the post-test, with a significance value of 0.00 obtained from the paired sample t-test